On Returning to the Sea: Towards Belonging Through Land, Language, & Tactile Storytelling - Walker, Arielle (Auckland University of Technology, 2020)
Stories are intrinsically connected to acts of making with fibre. Customary knowledge is passed down in stories, songs, conversations held over the extraction of muka, the spinning of wool, the weaving of harakeke, the waulking of tweed: narratives woven into the fibre, textiles and text in one. These shared histories of craft and language tie cultural memories and communities together and are irrevocably bound to cultural identity. Through systematic colonisation, migration, and the industrialisation of making, stories and craft traditions have been altered, shifted, and lost over time. I seek to reconnect with these taonga through On returning to the sea. My art practice is positioned in the spaces that have formed through the interweaving of language and craft, engaging hand-crafted textiles, poetic writing, drawing, lens-based media, being-in-place, and non-linear narrative as methods of making. I reference lines of my tūpuna wāhine – female ancestors – and look towards my ancestral homelands. Embedded in indigenous methodologies – whakapapa, whatuora, pūrākau – this research explores how cross-disciplinary, process-driven, relational practices might enable new relationships to form with these traditions and homes. By looking to the past, returning to the waters from which we came, we can untangle the threads that bind us to our traditions; and in the act of re-weaving, find new pathways to reciprocal belonging.
Keywords: Ancestral practices; Storytelling; Textiles; Craft; Language; Whenua; Whakapapa; Whatuora; Pūrākau; Indigenous methodologies; Tūpuna wāhine; Taranaki; Scotland; Ireland; Shetland; Settler-indigenous; Textile poetics; Art practice; Poetry